Bacterial carbon-phosphorus lyase: products, rates, and regulation of phosphonic and phosphinic acid metabolism. - Wackett, L P (1987)
Carbon-phosphorus bond cleavage activity, found in bacteria that utilize alkyl- and phenylphosphonic acids, has not yet been obtained in a cell-free system. Given this constraint, a systematic examination of in vivo C-P lyase activity has been conducted to develop insight into the C-P cleavage reaction. Six bacterial strains were obtained by enrichment culture, identified, and characterized with respect to their phosphonic acid substrate specificity. One isolate, Agrobacterium radiobacter, was shown to cleave the carbon-phosphorus bond of a wide range of substrates, including fosfomycin, glyphosate, and dialkyl phosphinic acids. Furthermore, this organism processed vinyl-, propenyl-, and propynylphosphonic acids, a previously uninvestigated group, to ethylene, propene, and propyne, respectively. A determination of product stoichiometries revealed that both C-P bonds of dimethylphosphinic acid are cleaved quantitatively to methane and, furthermore, that the extent of C-P bond cleavage correlated linearly with the specific growth rate for a range of substrates. The broad substrate specificity of Agrobacterium C-P lyase and the comprehensive characterization of the in vivo activity make this an attractive system for further biochemical and mechanistic experiments. In addition, the failure to observe the activity in a group of gram-positive bacteria holds open the possibility that a periplasmic component may be required for in vivo expression of C-P lyase activity.